PERENCANAAN SUMBER DAYA MANUSIA KESEHATAN (SDMK) PUSKESMAS DI KABUPATEN JEMBER - Shofiah, Rizkiy; Prihatini, Dewi; Viphindrartin, Sebastiana (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2019)
Public health centers are the spearhead in the implementation of health services in Indonesia. Public health centers are the first level facilities that seek promotive and preventive services to achieve health status. The provision of health services must be supported by adequate health personnel to support the functioning of the community health center. In accordance with its function, public health centers must have at least five promotive and preventive personnel, namely laboratory, pharmaceutical, nutrition, public health, and sanitation analysts. The availability of health human resources (HRH) for public health centers, especially laboratory analysts, nutrition, public health, and sanitation, is still not evenly distributed in the Jember district health centers. HRK planning in Jember Regency is still focused on medical personnel. This research is an exploratory research with a qualitative approach that aims to determine the HRH planning process, especially the promotive and preventive public health centers. The informants in this study were the head of the public health center administration as part of staffing and additional informants, namely analysts, nutrition, public health, and sanitation staff. Based on the results of the study, public health centers still need personnel such as analysts, nutrition, and sanitation. The results of interviews with informants indicated that the community health center did not have a special HRH planning team. In the planning process, the community health center only carried out an analysis of the HRH needs and then submitted them to the Health Office which had an important role in the planning process to meet the HRH needs of the community health center. As an executor, the community health center can only accept the applicable policies. Public health centers cannot do their own recruits because of budget constraints. This is one of the obstacles that hinders community health centers in HRH planning. Another obstacle in the planning process is waiting for a decision from the Health Office to meet HRH needs and the use of forecasting methods that are not yet clear. This causes, there is no common perception among policy makers. Keyword: Public health center, HRH planning, preventive and promotive.